Intersectional analysis of gender employment gaps in multilingual wealthy regions - Alexandra Tomaselli (Cogent Social Sciences)
The gender employment gap is a widespread reality, albeit with significant differences between the Global North and South. In Europe, the World Economic Forum, in 2024, has predicted this gap may close in 134 years. Eurostat and the Gender Equality Index show that since 2010 gender equality in labour has been progressing slowly. National statistics show that some states perform better (e.g. Spain) than others (e.g. Italy). Substate statistics may show reverse situations in wealthy regions (e.g. Catalonia and South Tyrol). Although statistics have begun adopting an intersectional approach regarding, e.g. age, origins, and disability, they offer a limited picture. Moreover, statistics are stuck in the binary division of sex assigned at birth without considering the growing (i.e. more visible) nonbinary population. Hence, they conceal that part of the gender gap that refers to LGBTQIA+ individuals. In this frame, this article uses an intersectional lens to explore how gender, ethnicity, race, and other social drivers and external factors impact the gender employment gap even in wealthy regions with low unemployment rates. Simultaneously, it suggests expanding the understanding of the gender employment gap by including the perspective of LGBTQIA+ individuals, who, like women, remain among those sectors of society that are underrepresented in the labour market. This research ultimately contributes to the understanding of how a wide array of social drivers and external factors may eventually feed the gender employment gap into a vicious circle by considering factors, such as antigypsyism or gender-based violence, that are usually dealt with separately.